How to improve access to health care for Roma living in social exclusion: a concept mapping study - Svobodova, Ivana; Filakovska Bobakova, Daniela; Bosakova, Lucia; Dankulincova Veselska, Zuzana (International journal for equity in health, 2021)
BACKGROUND: Half of the people living in social exclusion in the Czech Republic are of Roma origin. The worse health of Roma could be partly explained by numerous barriers to accessing health care. Therefore, our study aimed to explore the perceptions of various stakeholders and experts who may have an impact on the inclusion of Roma and/or their access to health care on how to improve health care access for Roma living in social exclusion in the Czech Republic. METHODS: We conducted a concept mapping study and obtained data from 32 participants from health and social services, policymakers and others who were involved in different study phases (brainstorming, sorting, rating, interpretation). RESULTS: Out of 64 proposed measures sorted into six distinct clusters, 20 were rated as the most urgent and the most feasible and should be implemented with a priority to improve access to health care for Roma living in social exclusion. The proposed measures covered various topics, such as education and awareness of the target group as well as education and supervision of helping professionals, strengthening capacities and streamlining the health care system, health promotion and associated services and increasing the local and financial accessibility of health care. Overall, measures concerning the education and supervision of helping professionals were rated as both the most urgent and the most feasible. Individual priority measures targeted, for example, the health needs assessment of Roma living in social exclusion to set up interventions or to include topics such as participation, empowerment, cultural competence and communication training in the curricula of health care and helping professionals in postgraduate and continuing studies. CONCLUSIONS: Stakeholders proposed a set of relevant and acceptable measures that may help improve access to health care for Roma living in social exclusion. The way they rated the proposed measures reflects both the current unfavourable mainstream and public discourse concerning Roma living in social exclusion and the most acute policy issues identified by several European and national bodies.
Keywords: Young Adult; China; disparity zdravotní péče; Male; Health care access; kulturní kompetence; kulturně kompetentní péče; sociální inkluze; mladý dospělý; Delivery of Health Care; Policies; Adolescent; Social Isolation; zranitelné populace; Roma; Spatial Analysis; Adult; zdravotní politika; Aged; dospělí; Interventions; mužské pohlaví; senioři; vytváření pojmu; Romové; Vulnerable population; dostupnost zdravotnických služeb; Ethnicity; prostorová analýza; mladiství; Healthcare Disparities; Czech Republic; Concept mapping; senioři nad 80 let; lidé; ženské pohlaví; Humans; Social Inclusion; Culturally Competent Care; Concept Formation; Aged, 80 and over; sociální izolace; zdravotnická zařízení; Vulnerable Populations; Čína; Cultural Competency; poskytování zdravotní péče; Health Facilities; Female; Health Policy; lidé středního věku; Health Services Accessibility; Middle Aged